Reflexive Journaling on Emotional Research Topics: Ethical Issues for Team Researchers - Malacrida, Claudia (Qualitative health research, 2007)
Traditional epistemological concerns in qualitative research focus on the effects of researchers' values and emotions on choices of research topics, power relations with research participants, and the influence of researcher standpoints on data collection and analysis. However, the research process also affects the researchers' values, emotions, and standpoints. Drawing on reflexive journal entries of assistant researchers involved in emotionally demanding team research, this article explores issues of emotional fallout for research team members, the implications of hierarchical power imbalances on research teams, and the importance of providing ethical opportunities for reflexive writing about the challenges of doing emotional research. Such reflexive approaches ensure the emotional safety of research team members and foster opportunities for emancipatory consciousness among research team members.